Intensity of water consumption in separate water collection points of internal water supply system - D. E. Polivanov; A. A. Semenov (Vestnik MGSU)
Introduction. The applied calculation methods for predicting water consumption at the objects of capital construction, when designing them, are based on the assumption of the deterministic character of elementary expenses (that is, expenses by one consumer or a water collecting device), which significantly coarsens the calculation methods and makes it impossible to analyze in detail the modes of operation of the water supply system of the considered object. The article is devoted to the study of the nature of variability and evaluation of distribution laws of elementary water consumption values arising during the operation of a number of the most common types of water-dispensing devices.Materials and methods. In the course of the study, statistical data on water consumption in cold and hot water pipelines supplying water to the most common types of water collection devices for 27 days were obtained using sensors. The data were processed and analyzed using methods of probability theory and mathematical statistics. Data processing was performed in C# and R programmes developed by the author, and visualization of the results in Microsoft Excel.Results. The main numerical characteristics of the values of elementary water flow rates are determined. Graphs of the time series, distribution density and distribution function of values of second water flow for typical cases are constructed. The distribution law is established and the analysis of the nature of the variability of the values of the second water flow for various types of water-dispensing devices is carried out, as well as a variant of their classification on this basis is proposed.Conclusions. The division of water-dispensing devices according to the character of variability of values of the second water flow rate into two groups is proposed: stochastic and conditionally deterministic. It is established that the value of the elementary flow rate for the first group of water-dispensing devices obeys the lognormal distribution, and for the second group it is a deterministic value.